Methods for rapid prototyping novel labware: using CAD and desktop 3D printing in the microbiology laboratory. (1st February 2022) - Diep, T.T.; Ray, P.P.; Edwards, A.D.
Abstract: Although the microbiology laboratory paradigm has increasingly changed from manual to automated procedures, and from functional to molecular methods, traditional culture methods remain vital. Using inexpensive desktop fused filament fabrication 3D printing, we designed, produced and tested rapid prototypes of customised labware for microbial culture namely frames to make dip slides, inoculation loops, multi‐pin replicators, and multi‐well culture plates for solid medium. These customised components were used to plate out samples onto solid media in various formats, and we illustrate how they can be suitable for many microbiological methods such as minimum inhibitory concentration tests, or for directly detecting pathogens from mastitis samples, illustrating the flexibility of rapid‐prototyped culture consumable parts for streamlining microbiological methods. We describe the methodology needed for microbiologists to develop their own novel and unique tools, or to fabricate and customise existing consumables. A workflow is presented for designing and 3D printing labware and quickly producing easy‐to‐sterilise and re‐useable plastic parts of great utility in the microbiology laboratory.